Phytophotodermatitis caused by Heracleum sosnowskyi with erythema multiforme-like lesions - Andrzej K. Jaworek; Karolina Michałek; Anna Wojas-Pelc (Termedia Publishing House, 2017)
Introduction. dermatitis bullosa pratensis (phytophotodermatitis) is an acute phototoxic reaction caused by photosensitizing substances present in different kinds of plants, activated by ultraviolet radiation exposure. An acute phototoxic reaction manifests as erythema, vesicles and even blisters with morphology of burns. Objective. We present a case report of phytophotodermatitis due to Heracleum sosnowskyi . Heracleum sosnowskyi was discovered in 1772 and described as a separate species in botanical literature in 1944 by I. P. Mandenova. Case report . In our case, skin lesions coexisted with erythema multiforme . Implemented therapy - corticosteroids, antihistamines and topical medications - was successful. After clinical resolution post-inflammatory hyperpigmentations were observed. Conclusions . Appropriate diagnosis of phytophototoxic reaction may constitute a challenge in everyday practice.